Characterization and Performance Evaluation of Dye Sensitized Solar Cell Using Nanostructured TiO2 Electrode - Sule Erten-Ela (International Journal of Photoenergy)
Metal-free organic sensitizer consisting of donor, electron conducting, and anchoring anhydride groups was engineered at molecular level and synthesized. Dye sensitized solar cells based on conjugated naphthalene dye were fabricated using nanoporous electrode. Photoelectrodes with a 7 μm thick nanoporous layer and a 5 μm thick light-scattering layer were used to fabricate dye sensitized solar cells. DSSCs were fabricated in a FTO/nc-TiO2/organic dye/I-/I3-/Pt/FTO device geometry. Dye sensitized solar cell was characterized by current density-voltage (J-V) measurement. All current-voltage (I-V) measurements were done under 100 mW/cm2 light intensity and AM 1.5 conditions. The photovoltaic data revealed a short circuit photocurrent density of 1.86 mA/cm2, an open circuit voltage of 430 mV, and a fill factor of 0.63, corresponding to an overall conversion efficiency of 0.53%.